The consequences of living longer—Effects of an experimentally extended velvet antler phase on the histomorphology of antler bone in fallow deer (Dama dama). Issue 5 (24th June 2021) - Kierdorf, Uwe; Schultz, Michael; Kierdorf, Horst
Abstract: Antlers are periodically regenerated paired cranial appendages of male deer (both sexes in reindeer) that constitute the fastest‐growing bones in the animal kingdom. The annual antler cycle of male deer is linked to testicular activity and largely controlled by seasonal fluctuations of testosterone concentrations in their blood. We studied the effects of an experimental doubling (to eight months) of the velvet antler phase, during which the antlers are covered by skin (velvet), on the histomorphology of antler bone in three adult fallow bucks. Extension of the velvet antler phase in the experimental animals had been caused by administration of the antiandrogen cyproterone acetate (CPA). The distal portions of the antlers from two of the CPA‐treated bucks exhibited partial sequestration of the antler cortex, with the separation plane typically located along the border between cortex and spongiosa. It is hypothesized that this was caused by cortical necrosis due to severe ischemia during later stages of the extended velvet antler phase. In places, new cancellous bone had been deposited on the resorption surface of the spongiosa, indicating a regeneration process. Normal fallow deer antlers ("controls") from this and a previous study, that is, antlers with a timespan of about four months between onset of new antler growth and velvet shedding, exhibited no or only minor bone remodeling and still contained remnants of calcified cartilage in their distal portions. In contrast, the antlers of the three CPA‐treated bucks showed evidence (secondary osteons and resorption cavities) of marked bone remodeling along their entire length and lacked remnants of calcified cartilage. Our results underscore that the typical histological features of antler bone reflect its short‐lived nature. Antlers are not mechanically loaded during the velvet stage, and it is presently unclear what triggered remodeling activity in the antlers whose lifespan had been experimentally extended. Abstract : Secondary osteons (arrows) and resorption cavities (arrowheads) indicate marked remodeling activity in a fallow deer antler with extended velvet antler phase due to treatment of the buck with the antiandrogen cyproterone acetate. PO: primary osteons. Transverse ground section viewed under circularly polarized light.